Running Speed is Maximized by Strengthening the Hip Flexors and Hip Adductors - Kaiwen Yang; Yi-Chung Lin; Marcus G. Pandy (Annals of Biomedical Engineering, 2026)
Purpose Cross-sectional studies indicate that sprint performance is strongly associated with leg-muscle strength, however there is no consensus on which muscles to strengthen to maximize running speed. The purpose of this study was to quantify and rank the sensitivity of maximum sprinting speed to changes in the strengths of individual leg muscles. Methods A full-body musculoskeletal model was combined with dynamic optimization theory to predict the effects of muscle strengthening on maximum sprinting speed. Results Maximum sprinting speed was most sensitive to a change in hip muscle strength: a 10% increase in hip strength increased maximum sprinting speed by 2.59% compared with 1.02% and 0.33% for the same change in ankle and knee strength, respectively. A 10% increase in hip strength increased step frequency by 2.24% and step length by just 0.4%. When muscles were grouped according to their anatomical function (e.g., flexors vs extensors), maximum sprinting speed was most sensitive to changes in hip-flexor strength: a 10% increase in hip-flexor strength increased maximum sprinting speed by 1.40% compared with 1.12% and 0.77% for the hip adductors and ankle plantarflexors, respectively. When individual muscles were strengthened in isolation, maximum sprinting speed was most sensitive to a change in iliopsoas strength: a 10% increase in iliopsoas strength increased maximum sprinting speed by 1.07% compared with 0.54, 0.44, 0.44 and 0.36% for adductor longus, adductor magnus, soleus, and gluteus maximus, respectively. Maximum sprinting speed was relatively insensitive ( Conclusion Strength training programs designed to maximize sprinting speed should focus on the hip flexors (iliopsoas) and hip adductors (adductor longus/magnus). Strengthening vasti, gluteus maximus, and hamstring will improve sprinting speed only marginally.

A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Groundtruthing nitrogen isotopes as a symbiosis proxy using the facultatively symbiotic coral Oculina arbuscula - Heather A. Donnelly; Maria Valadez-Ingersoll; Marcus Lin; Hanny E. Rivera; Carlos A. Tramonte; Sarah W. Davies; Xingchen Tony Wang (Frontiers in Marine Science, 2024)
The resilience of coral reefs in oligotrophic, (sub)tropical oceans is largely due to the symbiotic relationship between scleractinian corals and Symbiodiniaceae algae, which enables efficient internal nutrient recycling. Investigating the history of this coral symbiosis can provide insights into its role in sustaining the health of both present and future coral reefs. The isotopic composition of organic nitrogen ( 15 N/ 14 N or δ 15 N) bound within coral skeletons has been utilized to trace the existence of symbiosis in fossil corals, suggesting that coral symbiosis dates back to at least 210 million years ago. The basis of this proxy is that symbiotic corals are expected to exhibit lower δ 15 N compared to their non-symbiotic (aposymbiotic) counterparts within the same environments, owing to internal nitrogen recycling between the coral host and algal symbiont, and reduced leakage of low-δ 15 N ammonium into seawater. However, this hypothesis has not been adequately tested in contemporary settings. In a laboratory experiment, we examined the δ 15 N differences between the symbiotic and aposymbiotic branches within the same genetic backgrounds of the facultatively symbiotic coral Oculina arbuscula under well-fed conditions. Across five different genotypes in two separate experiments, symbiotic branches consistently showed lower δ 15 N than their aposymbiotic counterparts. These findings corroborate the use of δ 15 N as a proxy for identifying coral symbiosis in the past, particularly when multiple species of corals coexisted in the same environments.

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Load Distribution at the Patellofemoral Joint During Walking - Lucas T. Thomeer; Yi-Chung Lin; Marcus G. Pandy (Annals of Biomedical Engineering, 2020)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Correction to: Predictive Simulations of Neuromuscular Coordination and Joint-Contact Loading in Human Gait - Yi-Chung Lin; Jonathan P. Walter; Marcus G. Pandy (Annals of Biomedical Engineering, 2018)

Predictive Simulations of Neuromuscular Coordination and Joint-Contact Loading in Human Gait - Yi-Chung Lin; Jonathan P. Walter; Marcus G. Pandy (Annals of Biomedical Engineering, 2018)

Temperature effects on the activity, shape, and storage of platelets from 13-lined ground squirrels - Scott Cooper; Sarah Lloyd; Anthony Koch; Xingxing Lin; Katie Dobbs; Thomas Theisen; Matt Zuberbuehler; Kaley Bernhardt; Michael Gyorfi; Tanner Tenpas; Skyler Hying; Sarah Mortimer; et al. (Journal of Comparative Physiology B, 2017)

Direct Methods for Predicting Movement Biomechanics Based Upon Optimal Control Theory with Implementation in OpenSim - Sina Porsa; Yi-Chung Lin; Marcus G. Pandy (Annals of Biomedical Engineering, 2016)

Assessing production of the ubiquitous archaeal diglycosyl tetraether lipids in marine subsurface sediment using intramolecular stable isotope probing - Yu‐Shih Lin; Julius S. Lipp; Marcus Elvert; Thomas Holler; Kai‐Uwe Hinrichs (Environmental Microbiology, 2013)
Summary The membrane lipids diglycosyl‐glycerol dibiphytanyl glycerol tetraethers ( 2G ‐ GDGTs ) in marine subsurface sediments are believed to originate from uncultivated benthic archaea, yet the production of 2G ‐ GDGTs from subseafloor samples has not been demonstrated in vitro . In order to validate sedimentary biosynthesis of 2G ‐ GDGTs , we performed a stable carbon isotope probing experiment on a subseafloor sample with six different 13 C ‐labelled substrates (bicarbonate, methane, acetate, leucine, glucose and S pirulina platensis biomass). After 468 days of anoxic incubation, only glucose and S . platensis resulted in label uptake in lipid moieties of 2G ‐ GDGTs , indicating incorporation of carbon from these organic substrates. The hydrophobic moieties of 2G ‐ GDGTs showed minimal label incorporation, with up to 4‰ 13 C enrichment detected in crenarchaeol‐derived tricyclic biphytane from the S . platensis ‐supplemented slurries. The 2G ‐ GDGT ‐derived glucose or glycerol moieties also showed 13 C incorporation (Δδ 13 C = 18–38‰) in the incubations with glucose or S . platensis , consistent with a lipid salvage mechanism utilized by marine benthic archaea to produce new 2G ‐ GDGTs . The production rates were nevertheless rather slow, even when labile organic matter was supplied. The 2G ‐ GDGT turnover times of 1700–20 500 years were much longer than those estimated for subseafloor microbial communities, implying that sedimentary 2G ‐ GDGTs as biomarkers of benthic archaea are cumulative records of past and present generations.

Resource manipulation effects on net primary production, biomass allocation and rain-use efficiency of two semiarid grassland sites in Inner Mongolia, China - Ying Zhi Gao; Qing Chen; Shan Lin; Marcus Giese; Holger Brueck (Oecologia, 2011)

Nitrogen availability in a grazed semi-arid grassland is dominated by seasonal rainfall - Marcus Giese; Ying Zhi Gao; Shan Lin; Holger Brueck (Plant and Soil, 2011)

Effects of N and water supply on water use-efficiency of a semiarid grassland in Inner Mongolia - Holger Brueck; Klaus Erdle; Yingzhi Gao; Marcus Giese; Ying Zhao; Stephan Peth; Shan Lin (Plant and Soil, 2010)

Belowground net primary productivity and biomass allocation of a grassland in Inner Mongolia is affected by grazing intensity - Ying Zhi Gao; Marcus Giese; Shan Lin; Burkhard Sattelmacher; Ying Zhao; Holger Brueck (Plant and Soil, 2008)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)